[Behind the Society of Black Engineers and Scientists fundraiser booth] (1992)
Members of the Society of Black Engineers and Scientists at their booth. One member with a colorful blouse is sitting low in their chair. Three other members are behind her, one wearing blue, another in a white shirt and the last one wearing a black shirt.